“WE ARE HISPANIC AMERICANS, THE PEOPLE FROM ABROAD”: SMALL TEST ON LITERARY PRACTICES AND FREEDOM EXCHANGES BETWEEN BRAZIL AND LATIN AMERICA - Tavares, Mariana Rodrigues (Revista de Historia Social y de las Mentalidades, 2021)
This article is intended to approach the relative issues between the book exhibitions held between Brazil and Latin American countries throughout the 20th century. In addition, it demonstrates the work of the Instituto Nacional do Livro (INL) as a producer of books, collections that were intended to disseminate Brazilian culture, thus inscribing themselves in the national pedagogical practice of the Estado Novo (1937-1945). In view of the obscurantism that permeates the social history of the Instituto Nacional do Livro and the very lack of other historiographical researches dedicated to this theme, the present work presents itself as a valuable contribution on the editorial circuits that permeated important chapters of the circulation of print in the Brazil and Latin America. Keywords: ; ; Latin America.
Keywords: Instituto Nacional do Livro; Books; Literate Exchanges; América Latina